(untitled) (Research, Society and Development, 2021)
To analyze trends, and the main socioeconomic and clinical factors related to treatment abandonment and the cure of leprosy in Sergipe. For the present study, data from all new cases of cure and abandonment of leprosy treatment notified by the health centers of the municipalities to the SINAN (Information System on Notifiable Diseases) in the state of Sergipe, Brazil, from 2007 to 2017, were used. This is an ecological study of cases of cure and abandonment of leprosy treatment, rates were calculated based on the "Guidelines for surveillance, care and elimination of leprosy as a public health problem".using time-series analysis and multivariate logistic regression. Concerning multivariate regression, the young age group presents a higher risk for quitting the treatment (p = 0.429; OR = 2.75). Blacks/browns/indigenous were more likely to abandon treatment (p = 0.482; OR = 1.69), as well as multibacillary individuals (p = 0.541; OR = 2.26). Regarding the cure, the young age group has less chances of cure (OR = 0.34). The same happens for the operational classification; the multibacillary patients have a lower chance of cure (OR = 0.35). Finally, individuals with grade 2 of physical disability are less likely to be cured (OR = 0.54). Health services are noticeably weak, especially when it comes to clinical factors associated with treatment abandonment and a low proportion of cure. Multibacillary (Borderline and Lepromatous) are responsible for the active transmission of leprosy.